+0  
 
0
256
1
avatar

Algebra 2 help!!!!!!!!

Guest Oct 3, 2017
 #1
avatar+7266 
+1

Here is option one:

 

f(x)  =  (x - 1)(x - 3)(x - 5)  =  (x - 1)(x2 - 8x + 15)  =  x3 - 9x2 + 23x - 15

 

f(x)  =  x3 - 9x2 + 23x - 15

 

We can multiply the previous polynomial by any number and the resulting polynomial will have the same zeros....I picked  -2. Here is option two:

 

f(x)  =  -2(x - 1)(x - 3)(x - 5)  =  -2(x3 - 9x2 + 23x - 15)  =  -2x3 + 18x2 - 46x + 30

 

f(x)  =  -2x3 + 18x2 - 46x + 30

 

Here's a graph with these two functions on it:   https://www.desmos.com/calculator/lmrqxh79cx

hectictar  Oct 3, 2017

5 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.